Torture of Suspects in The Investigation Process - Rifaldi W. Hasim (Universitas Negeri Gorontalo, 2022)
Abstract: This study aims to analyze the juridical review of acts of violence committed by investigators against suspects in the investigation process at the Bone Bolango Resort Police, as well as to examine the factors that led to violent acts committed by investigators against suspects in the investigation process at the Bone Bolango Resort Police. This type of research is juridical empirical. The approaches used by researchers in compiling this research are, among others: the Legislative Approach (Statue Approach) and; the Case approach (case approach). The results of the study indicate that the use of violence in the investigation process is prohibited because the suspect still has rights attached to him and guaranteed by the state through Law Number 8 of 1981 concerning the Criminal Procedure Code (Book of the Criminal Procedure Code). The use of violence in the investigation process is caused by the ignorance of the suspect/defendant regarding the law and the rights that are still attached to it.